Model Optimisasi Multiobjektif untuk Masalah Alokasi Penggunaan Lahan dengan Menggunakan Analisis Data Spasial - Diah Chaerani; Budi Nurani Ruchjana; Vivian Wilhelmina (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2012)
A good land-use allocation is an important effort to create a safe urban space, comfortable, productive, and sustainable. This is as stipulated in UU RI No. 26 of 2007 regarding spatial planning in Indonesia. Therefore the optimization on allocation land use is important to do. In this paper we present a different approach to solve the land-use allocation problem, i.e,, by using multiobjective optimization, branch and bound methods and generating spatial data analysis via uniformly weighted matrix. In this problem, the objective function is to maximize the total density index and total comprehensive index of the land-use types. An illustrative data that refer to Region Regulation for Bandung No. 09 of 2009 is presented.